(untitled) (Third Sector Social Economic Review, 2017)
This study aims to determine the way the phenomenon of leadership and participatory leadership are evaluated by members from their perspectives with positive a well as negative aspects, to raise awareness, and to determine how members look at participatory leadership and their views on leadership. Ankara team of Search and Rescue Association (AKUT) with its approximately 2110 volunteering members active in 36 different points in Turkey was chosen as the study group. AKUT Ankara Team has 96 members who are summoned in cases of emergency.13 participants were interviewed face-to-face. Each participant was asked to answer the same questions; their answers were listened from the beginning to the end, and were transcribed to read later. The responses were listed, and efforts were made to set up ties between them. Content analysis was used in order to make a synthesisof the participants’ diverse perspectives. The findings demonstrated that the first characteristic of participatory leadership was being together with the members with no distance of power, and which was followed by being open to communication without obstacles, considering changes and implementing them respectively. And it was found that the final characteristic was the harmony between members by means of these components and synergy.